High-sensitivity cardiac troponin and natriuretic peptide with risk of lower-extremity peripheral artery disease: the Atherosclerosis Risk in Communities (ARIC) Study. (22nd March 2018) - Matsushita, Kunihiro; Kwak, Lucia; Yang, Chao; Pang, Yuanjie; Ballew, Shoshana H; Sang, Yingying; Hoogeveen, Ron C; Jaar, Bernard G; Selvin, Elizabeth; Ballantyne, Christie M; Sharrett, A Richey; Folsom, Aaron R; et al.
Abstract: Aims: Cardiac troponin T (cTnT) is suggested as a predictor of amputation in patients with peripheral artery disease (PAD). However, cTnT-PAD association has not been systematically studied in a large study. This study evaluated the association of high-sensitivity cTnT (hs-cTnT) with PAD incidence and also explored whether natriuretic peptide (NT-proBNP), another representative cardiac marker, predicts PAD risk. Methods and results: Among 12 288 middle-aged adults, the associations of hs-cTnT and NT-proBNP with incident PAD (hospitalizations with PAD diagnosis or leg revascularization [cases with rest pain or tissue loss considered as critical limb ischaemia (CLI)]) were quantified with multivariable Cox regression models. The risk discrimination was assessed by c-statistic. During a follow-up over 22 years, 454 participants developed PAD (164 CLI cases). In demographically adjusted models, the highest category of hs-cTnT (≥14 vs. <3 ng/L) and NT-proBNP (≥258.3 vs. <51.5 pg/mL) showed ∼8- and 10–20-fold higher risk of PAD and CLI, respectively. Even after adjusting for potential confounders and each other, hazard ratios were greater for CLI than for PAD (7.74 95% confidence interval [95% CI 4.43–13.55] vs. 2.84 [2.02–4.00] for the highest vs. reference hs-cTnT category and 4.63 [2.61–8.23] vs. 3.16 [2.23–4.49] for the highest vs. reference NT-proBNP category). The addition of these cardiac markers improved c-statistics for CLI. Conclusion: High-sensitivity cTnT and NT-proBNP were independently associated with incident PAD, particularly its severe form, CLI. Although future studies are warranted to investigate pathophysiological mechanisms behind these associations, our study suggests the usefulness of cardiac markers to identify individuals at high risk of CLI.